Actoprotective properties of 7’-((3-thio-4-methyl-4H-1,2,4-triazole-5-yl)methyl)theophylline derivatives - Gotsulya, A. S. (Zaporozhye Medical Journal, 2016)
The aim of this work was the study of actoprotective activity of compounds, which combine sintons of 1,2,4-triazole-3-thiol and theophylline. Materials and methods. The first time synthesized 7’-((3-thio-4-phenyl-4H-1,2,4-triazole-5-yl)methyl)theophylline derivatives have been used for the research. The systemic toxicity and the acute toxicity of the studied compounds have been performed by the rapid method of Prozorovskiy to determine the optimal conditions for dispensing substances. Experiments have been conducted on a group of white nonlinear rats, 159–221 g weight. During the study of actoprotective activity the method of forced immersion in water with a load of 10% by weight of the rats has been used. The substances were administered at a dose 1/10 of LD50, and the reference drug «Riboxin» at a dose of 100 mg/kg. The swim time was recorded in seconds. The control group of animals was used for comparison; these animals received saline solution intraperitoneally 20 minutes before immersion. The obtained results were statistically processed using the standard software package of Microsoft Office 2007 and «STATISTICA@ for Windows 6.0». Results. According to the results of conducted researches it has been established that the most active compound among the studied was 7’-((5-(2-hydroxyethylthio)-4-phenyl-4H-1,2,4-triazole-3-yl)methyl)theophylline, which increased the duration of swimming by 14.31% comparing to control group, whereas the reference drug increased it by 20.57%. It has been established that 2-((5-((theophylline-7’-yl)methyl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio)-N’-(3,4-difluorobenzylidene)acetohydrazide also increases the duration of swimming. Conclusion. The study of actoprotective activity of 13 first time synthesized compounds has been conducted. 7’-((5-(2-Hydroxyethylthio)-4-phenyl-4H-1,2,4-triazole-3-yl)methyl)theophylline has been detected as the most active compound among the studied ones.